Chatbots : Friends or Fiends ? - Suguna, V S (2017)
The world is seeing how Internet technologies can facilitate crime and terrorism for the purposes of victimisation, illicit communication and online radicalisation. As advances in Artificial Intelligence (AI) drive the growing adoption of chatbots, it may be a matter of time before threat actors jump on the bandwagon to stay ahead of law enforcement and security agencies.